2022
DOI: 10.1155/2022/4499876
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Cells-Derived Extracellular Vesicles Containing microRNA-146a-5p Affect Actin Dynamics to Promote Cervical Cancer Metastasis by Activating the Hippo-YAP Signaling Pathway via WWC2

Abstract: Application of extracellular vesicles (EVs) for cancer treatment has been well-documented. We probed into the potential role of cervical cancer cells-secreted EVs by transferring miR-146a-5p in cervical cancer. After characterization of miR-146a-5p expression in clinical cervical cancer tissue samples, gain- and loss-of-function experiments were implemented to test the effect of miR-146a-5p on the invasion, epithelial-mesenchymal transition (EMT), and anoikis in cervical cancer cells. EVs were isolated from hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is the second leading cause of cancer-related death in women between the age of 20–39 [ 139 , 140 ]. A recent study showed that EV-carrying miR-146a-5p promotes the lung metastasis of CC cells by suppressing WWC2 expression, inhibiting the phosphorylation of cofilin, and changing the depolymerization of F-actin/G-actin, thereby activating the Hippo–Yap signaling pathway [ 93 ]. Certain studies have shown that circRNAs can act as an oncogene and tumor suppressor for the progression and metastasis of CC [ 141 , 142 ].…”
Section: Emerging Functions Of Ev-derived Ncrnas In Organ-specific Me...mentioning
confidence: 99%
“…It is the second leading cause of cancer-related death in women between the age of 20–39 [ 139 , 140 ]. A recent study showed that EV-carrying miR-146a-5p promotes the lung metastasis of CC cells by suppressing WWC2 expression, inhibiting the phosphorylation of cofilin, and changing the depolymerization of F-actin/G-actin, thereby activating the Hippo–Yap signaling pathway [ 93 ]. Certain studies have shown that circRNAs can act as an oncogene and tumor suppressor for the progression and metastasis of CC [ 141 , 142 ].…”
Section: Emerging Functions Of Ev-derived Ncrnas In Organ-specific Me...mentioning
confidence: 99%